Faktor Risiko Kejang Demam Berulang pada Anak - Prastiya Indra Gunawan; Darto Saharso (MEDIA MEDIKA INDONESIANA, 2012)
Risk factors of recurrent febrile seizures in childrenBackground: Febrile seizures (FS) are the most common seizure disorder in childhood. Recurrent febrile seizures (RFS) occur in one third of children who experience a first FS. About nine percent had three or more recurrence. Little is known about predictors of recurrence. The aim of this study is to determine the incidence and the risk factors of RFS in children with FS at Dr. Soetomo Hospital Surabaya.Method: This is a cohort prospective study. Data was taken from all children with first FS aged 6 month-old to 5 year-old who were admitted at pediatric ward Dr. Soetomo Hospital from August 2009 to November 2010. They were observed for one year period to ascertain wether FS recurred. Logistic regression statistic was used to analyze those variables including sex, age, body temperature during the fever episode, family history of seizures, diagnosis at the first onset, maternal illness, abnormal delivery and recurrence ofFS.Results: Recurrent FS occured in 65% of the 100 children at one year observation, and 26% of them had further attack. Male to female ratio was 2:1. Thirty-one (77.5%) of subjects were less than 12 months-old. Body temperature ≤38.5OC (OR=5.50, 95%CI, p=0.019) and complex FS (OR 5.03, 95%CI, p=0.025) were related to increase risk of reccurence.Conclusions: The risk of RFS increased with body temperature ≤38.5OC and diagnosed as complex FS at the first FS.Keywords: Children, risk factors, recurrent febrile seizures ABSTRAKLatar belakang: Kejang demam (KD) adalah kasus kejang yang sering dialami anak-anak. KD berulang terjadi pada sepertiga anak yang mengalami KD pertama. Sekitar 9% dari penderita KD mengalami tiga atau lebih kejadian berulang. Hanya sedikit yang diketahui tentang prediktor berulangnya KD. Tujuan penelitian untuk mengetahui angka kejadian KD berulang dan menentukan faktor risiko terjadinya KD berulang pada anak yang mengalami KD di RSUD Dr. Soetomo Surabaya.Metode: Studi kohort prospektif dilakukan pada bulan Agustus 2009 sampai November 2010. Subyek diambil dari anak usia 6 bulan sampai 5 tahun yang menderita KD pertama yang MRS di RSUD Dr. Soetomo. Subyek diamati selama 1 tahun untuk menentukan apakah KD terjadi berulang. Analisis antar variabel jenis kelamin, usia, suhu badan saat terjadi demam, riwayat kejang pada keluarga, diagnosis awal, penyakit ibu, kelahiran yang tidak normal dan kejadian KD berulang, dilakukan dengan regresi logistik.Hasil: KD berulang terjadi 65% pada 100 anak yang diobservasi selama 1 tahun pertama dan 26% mengalami KD lebih dari 2 kali. Rasio laki-laki dibanding perempuan adalah 2:1. Tiga puluh satu (77,5%) anak berusia kurang dari 12 bulan. Faktor risiko suhu badan ≤38,5OC (OR=5,50, 95%CI, p=0,019) dan KD komplikata (OR 5,03, 95%CI, p=0,025) bermakna secara signifikan untuk kejadian berulangnya KD.Simpulan: Risiko KD berulang pada anak meningkat pada suhu badan ≤38,5OC dan diagnosis KD komplikata pada saat KD pertama.